MODERN METHODOLOGY OF TEACHING STUDENTS USING A CREATIVE APPROACH IN TEACHING ENGLISH - Talipova Nilufar Abduvasikovna (Web of Journals Publishing, 2025)
This article discusses the importance of teaching students using a creative approach in teaching English, as well as the current interest in teaching and learning foreign languages in educational institutions and non-state higher education institutions in our country, with the help of modern technologies, new A comparative analysis of fundamental, linguo-sociocultural, and communicative methods was conducted using methodologies. The role and importance of teaching students using a creative approach in the educational process were scientifically demonstrated and explained.
Keywords: Teaching, methods, innovation, creativity, speaking skills, innovation, methodology, innovation, foreign language, communication, innovative technology, technological tools, methods.